Analysis of the Framing of Anies Baswedan's Formula-E News in Liputan6.com and Republika.co.id Media - Oktaviant, Nur Rizqi Puta Nanda Elang; Sufyanto, Sufyanto (Procedia of Social Sciences and Humanities, 2024)
This study analyzes the framing used by two leading online media, Liputan6.com and Republika.co.id, in reporting on the Formula E case involving Anies Baswedan, a prominent political figure in Indonesia. Using a qualitative approach with the Pan & Kosicki framing analysis method, this study reveals how the two media frame the issue differently, which ultimately affects the public's perception of Baswedan. The results showed that Liputan6.com tended to portray Baswedan as a cooperative figure but under political pressure, while Republika.co.id emphasized the narrative that Baswedan was a victim of an unfair process. Through the choice of words, information structure, and the use of visuals, these two media play a significant role in shaping public opinion regarding the figure of Anies Baswedan. This research highlights the importance of understanding media framing as a highly effective tool in influencing public opinion, especially in the context of controversial and dynamic issues such as Baswedan's candidacy in the 2024 Presidential Election and his involvement in the Formula E case.